Getting Right with Reagan : The Struggle for True Conservatism, 1980-2016 - Witcher, Marcus M. (Book collections on Project MUSE., 2019)
"Ronald Reagan has become synonymous with conservatism and continues to be lionized as the shining representative of the movement. But the fortieth president was no conservative ideologue. He had a complex relationship with American conservatives, and to many of his most ardent supporters he was not conservative enough. Critics complained during his time in office that he failed to bring about the promised Reagan Revolution, and in 1988 Republican presidential hopefuls ran to the right of his policies. Following Reagan's years in office, however, conservative assessments of his presidency quickly improved as subsequent presidents made comparatively fewer achievements. Over time a mythical version of Reagan as an ideological purist began to form in the minds of many conservatives, who forgot his pragmatic governing style and sought to use his legacy for their own political purposes. The mythical, dogmatic Reagan has played an important role in the conservative turn in the Republican Party over the last three decades, ultimately coming to an end with the election of Donald Trump. Getting Right with Reagan: The Struggle for True Conservatism, 1980-2016 seeks to uncover the real Reagan behind the myth and explain how the president has been misunderstood and misused by conservatives in the years since he was in office. Marcus M. Witcher argues that contemporary Republican politics and politicians are defined by their interpretation of Reagan. How conservatives remember the 1980s, and how they frame Reagan's legacy, has shaped the evolution of the GOP. The story of their interpretation of Reagan is also the story of the transformation of the Republican Party and the evolution of the conservative movement"--